NORTHERN ARIZONA PROPOSED WITHDRAWAL OF FEDERAL MINERAL ESTATE, COCONINO AND MOHAVE COUNTIES, ARIZONA. [Part 69 of 75] (EPA number: 110359, Final EIS--1,092 pages, Appendices--available electronically, October 28, 2011, 2011)
PURPOSE: The withdrawal of approximately one million acres of federal mineral estate in northern Arizona from the location of new mining claims under the General Mining Law of 1872 is proposed. The uranium deposits within the northern Arizona breccia pipes are of higher grade than approximately 85 percent of the worlds known uranium deposits and the lands within the proposed withdrawal area are considered to have a high potential for uranium. The planning area includes 626,678 acres of public lands managed by the Bureau of Land Management, 355,874 acres of lands managed by the Kaibab National Forest, 4,204 acres administered by the Arizona State Land Department, and 19,789 acres of private land. The proposed withdrawal is the result of concerns over potential impacts of uranium mining on the Grand Canyon watershed adjacent to and including Grand Canyon National Park. As of July 2009, these lands were segregated for up to two years from location and entry of new mining claims. On June 27, 2011, the Secretary of Interior published an emergency withdrawal which will expire on January 20, 2012, to allow the lands to remain closed to location and entry during the completion of the National Environmental Policy Act process. Four alternatives, including a No Action Alternative (Alternative A), are considered in this final EIS. Under Alternative A, there would be no withdrawal and location and recordation of mining claims would continue. Alternative B, the preferred alternative, is the proposed action to withdraw 1,006,545 acres from location and entry for 20 years, subject to valid existing rights. Alternative C would involve a smaller withdrawal of 650,333 acres and Alternative D would involve a further reduced withdrawal of 295,991 acres. Both the current segregation and the proposed withdrawal apply only to public domain federal mineral estate, including federal mineral estate underlying non-federal surface lands. Neither the current segregation order nor the proposed withdrawal apply to non-federal mineral estate or to leasable or salable minerals such as oil and gas leasing, and sand and gravel permits. POSITIVE IMPACTS: The withdrawal of the parcels from new mining claims would protect the natural, cultural, and social resources in the Grand Canyon watershed from the possible adverse effects of the reasonably foreseeable locatable mineral exploration and development that could occur in the segregated area. NEGATIVE IMPACTS: Mine operations would impact air quality, soil resources, vegetation, and aquatic and terrestrial habitats. Numerous cultural sites could be affected and mining-related roads would adversely impact users seeking primitive recreation opportunities in adjacent areas. Alternatives B, C, and D are projected to reduce annual government revenues by $16.6 million, $10.5 million and $3.5 million, respectively, compared to Alternative A. Alternatives B, C and D are projected to decrease uranium mining-related employment by 465 jobs, 294 jobs and 104 jobs, respectively. The reduction in uranium production under Alternative B would be equivalent to about six percent of current U.S. demand. Uranium production would be reduced by about four percent of current U.S. demand under Alternative C and about two percent of current U.S. demand under Alternative D. LEGAL MANDATES: Federal Land Policy and Management Act of 1976 (43 U.S.C. 1701 et seq.) and General Mining Law of 1872 (30 U.S.C. 21 et seq.).